The SAGE handbook of consumer culture - Kravets, Olga; Maclaran, Pauline; Miles, Steven; Venkatesh, Alladi (Los Angeles : SAGE Publications Ltd, 2018)
The question of consumption emerged as a major focus of research and scholarship in the 1990s but the breadth and diversity of consumer culture has not been fully enough explored. The meanings of consumption, particularly in relation to lifestyle and identity, are of great importance to academic areas including business studies, sociology, cultural and media studies, psychology, geography and politics. The SAGE Handbook of Consumer Culture is a one-stop resource for scholars and students of consumption, where the key dimensions of consumer culture are critically discussed and articulated.
'SAGE reference.'
Includes bibliographical references at chapter ends, and index.
Keywords: Consumer behavior -- Handbooks, manuals, etc; Culture -- Economic aspects -- Handbooks, manuals, etc; Consumption (Economics) -- Social aspects -- Handbooks, manuals, etc